(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
This paper proposes the utilization of a fuzzy database engine for supporting medical diagnoses. Expert know how is stored in a relational database and then it is modeled diagnoses rules with fuzzy queries that pulls out the most accurate information related to the sickness and therefore supporting doctors with the medical diagnostic. A solution prototype has been developed with information related to respiratory disease characterization and it is built with fuzzy queries using SQLf. This case study can be used to define a roadmap for future developments in medical diagnosis supported on fuzzy databases. As always, the diagnosis can only be given by a specialist, these systems only provide help in their work task.